Analytical method for profiling of radial stator blades of turbine stages - Rusanov, R.A.; Rusanov, A.V.; Lampart, P.; Chugay, M.A. (Проблемы машиностроения, 2016)
The method of analytical profiling of radial stator blades is considered, which in combination with numerical modelling of three-dimensional viscous flows allows us to improve the efficiency of the flow part of high-loaded centripetal turbines. The profile of radial blades is determined in a curvilinear coordinate system and consists of the trailing and leading edges, and also of suction and pressure sides described by polynomial curves of the 5th and 4th order, respectively. Thanks to this method, highly efficient radial stator blades of high-loaded stages can be designed. The special form of blade-to-blade channels allows us to obtain a low level of profile and trailing edge losses, as well as low supersonic and shock wave losses of kinetic energy. Three variants of turbines with different types of stator blade profiles are considered: the profile developed using a standard method for axial blades; the “half-drop” profile and the profile developed using the proposed method. For the stator profile developed in this paper, the stator kinetic energy losses related to the enthalpy drop in the stage were decreased by 2,2% compared to the profile of a classic form, and by 1,1% compared to the “half-drop” profile. Using of the high-loaded stage with a new type of stator blade profile allowed us to significantly improve the aerodynamic characteristics of the flow part in the whole stage. Рассмотрен метод аналитического профилирования радиальных лопаток направляющих аппаратов, использование которого в сочетании с численным моделированием трехмерных вязких течений позволяет повысить эффективность проточных частей высоконагргженных центростремительных турбин. Запропоновано аналітичний метод побудови профілів радіальних лопаток турбінних ступенів. Профіль задається в криволінійній системі координат, складається з вхідної та вихідної кромок, а також спинки і коритця, описаних кривими 5-го та 4-го порядків відповідно. Розглянуто приклад високонавантаженого радіально-осьового ступеня з профілем направляючого апарата нового типу, застосування якого дозволило істотно поліпшити аеродинамічні характеристики проточної частини.